The effects of adiponectin and inflammatory cytokines on diabetic vascular complications in obese and non-obese patients with type 2 diabetes mellitus. (January 2016) - Hong, Seong Bin; Lee, Jung Jin; Kim, So Hun; Suh, Young Ju; Han, Ju Young; Kim, Yong Seong; Nam, Moonsuk
Highlights: Patients with type 2 diabetes were divided into an obese and non-obese group. Associations between adipokines and vascular complications were assessed in each group. Serum total adiponectin may influence proliferative retinopathy in the obese group. Abstract: Aims: To evaluate the associations between inflammatory cytokines and adiponectin and various vascular complications in type 2 diabetes mellitus (T2DM). Methods: A total of 761 patients with T2DM were divided into a non-obese group and an obese group to enable the effects of obesity and T2DM on vascular complications to be differentiated. The serum levels of circulating inflammatory cytokines, that is, tumor necrosis factor (TNF)-α, and interleukin (IL)-6, total adiponectin, and high molecular weight (HMW) adiponectin were measured, and carotid intima media thickness (IMT), the presence of carotid plaque, and the severities of retinopathy and nephropathy, were assessed. Results: The obese group had significantly lower serum total and HMW adiponectin levels than the non-obese group. In the obese group, serum levels of total and HMW adiponectin, and TNF-α were significantly higher in patients with proliferative retinopathy than in those without retinopathy after adjusting for covariates. In the non-obese group, only IL-6 levels were significantly higher in patients with proliferative retinopathy than in those without. Serum levels of total and HMW adiponectin were significantly higher in patients with macroalbuminuria than in those with normoalbuminuria. No significant difference of three cytokines levels were observed depending on the carotid IMT or the presence of plaque. Logistic regression analysis revealed that serum total adiponectin (OR = 1.209, P = 0.038), diabetes duration (OR = 1.230, P = 0.014), and HbA1c (OR = 2.359, P = 0.006) were significantly associated with proliferative retinopathy in the obese group. Conclusion: The study shows total adiponectin may influence proliferative retinopathy in obese patient with T2DM.